TI_GERICHTE 17.2018.123 vom 4. Oktober 2018 , Ripetuto furto di poca entità. Accertamento dei fatti. Verità materiale. - TI Tribunale d'appello (2018)
Ripetuto furto di poca entità. Accertamento dei fatti. Verità materiale.